Somatic mutation and the Antarctic ozone hole - Laurence Clarke; Ayre, DJ; Robinson, SA (2008)
1 Previous studies of Antarctic clonal moss populations using RAPD markers have reported extraordinarily high levels of genetic variation. This has been claimed to reflect somatic mutation, possibly resulting from elevated UV-B radiation. 2 Our study used microsatellite markers to compare the genetic variation present within continental Antarctic, sub-Antarctic and temperate populations of the moss Ceratodon purpureus . 3 In contrast to the RAPD studies, microsatellite data revealed that C. purpureus populations from continental Antarctica display less intra-population genetic diversity than populations from a range of temperate and sub-Antarctic sites. 4 Analysis of molecular variation (amova) revealed that populations within the Windmill Islands region of Antarctica were more genetically differentiated than populations spread among more widely separated temperate regions. 5 Synthesis . Our data provide no evidence of elevated mutation rates in the Antarctic, and imply climate change will present ongoing challenges for continental Antarctic moss populations that appear weakly interconnected and with less potential than temperate populations to adapt to environmental change.